Pelaksanaan Kegiatan Ekstrakurikuler Marching Band di SMA Negeri 7 Padang - Leisya Nizora; Tulus Handra Kadir (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to find out and describe the implementation of marching band extracurricular activities at SMA Negeri 7 Padang. This type of research is qualitative research with a descriptive method. The research instrument is the researcher himself and is assisted by supporting instruments such as stationery and cameras. Data were collected through literature studies, observations, interviews and documentation. The steps of analyzing data are data collection, data reduction, data presentation and drawing conclusions. The results of the study show that the factors that affect students' interest in learning dance in dance extracurricular at Adabiah Padang High School consist of internal factors and external factors. Internal factors are students' attention to dance extracurricular materials is very good, students' attitudes towards dance extracurricular activities are good, students' ability to perform dance movements is not good and students' interest in dance extracurricular activities is good. Meanwhile, the external factors are that the dance extracurricular coordinator at Adabiah Padang High School is not good and the infrastructure at the school is relatively low.